How can we transform citizens into ‘environmental agents of change'? Towards the citizen science for environmental citizenship (CS4EC) theoretical framework based on a meta-synthesis approach - Hadjichambis, Andreas Ch.; Paraskeva-Hadjichambi, Demetra; Georgiou, Yiannis; Adamou, Anastasia (My University, 2023)
Environmental Citizen Science (CS) initiatives are argued to provide a promising vehicle for involving citizens in the investigation of various socio-environmental issues. However, environmental CS initiatives have often been criticized for merely focusing on the achievement of their scientific goals and outcomes (science-oriented), rather than on empowering and transforming the participants into ‘environmental citizens’ (citizen-oriented). This study adopts a meta-synthesis approach to synthesize evidence from three recent systematic reviews, seeking to extract a set of design principles for the development of an integrated theoretical framework enabling Environmental Citizenship (EC) in environmental CS initiatives. The proposed framework lies on the intersection of three main research areas: (a) Participation in CS, (b) Pedagogy in CS, and (c) Education for Environmental Citizenship. Grounded on the conjunction of the aforementioned areas, the Citizen Science for Environmental Citizenship (CS4EC) framework puts forward the transformative capacity and the participatory learning aspects of environmental CS initiatives. Overall, the proposed framework lays the foundations for the design of environmental CS initiatives capable for the empowerment and transformation of citizens into ‘environmental agents of change’.
Keywords: citizen science (CS) initiatives; Citizen Science for Environmental Citizenship; environmental citizenship; meta-synthesis; theoretical framework